Manajemen Jalan Napas Definitif pada Pasien Gawat Darurat - Cholyviona W.S Handhayani; Sidharti, Liana; Wahyuni, Ari (CV. Jasa Sukses Abadi, 2024)
Definitive airway refers to the creation of a safe and patent airway to ensure adequate gas exchange, usually involving the trachea and special airway devices. Definitive airway is the standard of care in pre-hospital airway management, especially in trauma patients. Definitive airway has an important aspect in airway management, especially in emergency and trauma care, and its implementation is essential to ensure patient safety and stability. Proper training and routine maintenance skills are key to increasing the success rate of airway management procedures. A definitive airway can be performed if a clinical picture is obtained, including guarantees for maintaining a patent airway, failure to maintain adequate oxygenation with an oxygen mask or the appearance of apnea, airway guarantees including respiratory failure (hypoxia or hypercapnia), the presence of a head injury and requiring broadcast assistance, and decreased consciousness with a GCS (Glasgow Coma Scale) score of 8 or less. Patients with serious or persistent airway compromise usually require an airway device. The most common devices used in definitive airway include orotracheal intubation, nasotracheal intubation, and surgical airway (cricothyroidotomy and tracheostomy). The choice of airway device and technique is tailored to the specific clinical scenario and patient condition.